Personalization in air travel : data-driven, technology-enabled, human-supported - Taneja, Nawal K. (Routledge, 2026)
Personalization is now becoming an emerging frontier for leading businesses worldwide. Customers want businesses to understand their specific needs and preferences so as to provide personalized products and services, as well as to provide them with some control over their experience. For businesses, personalization improves customer experience and customer loyalty, through better customer engagement. In the case of airlines, although progress in personalization is beginning to increase in some areas (in-flight services and the availability of personal digital assistants, for example), advancement in other important areas (such as seamless end-to-end journeys in the travel ecosystem, for example) has been slow and disjointed for a number of reasons. A few examples include the ongoing constraints of legacy infrastructure, granularity of data limitations, concerns relating to data privacy, lack of standards for measuring the tangible value of personalization provided and received, and the challenge of scaling personalization initiatives. Besides these examples of challenges, a key question is being raised. Can personalization, other than for the small segment of high-margin travellers, be a revenue driver, or would it merely increase complexity without proportionate returns?Taneja discusses ten key points for airlines who want to move up the personalization curve to offer personalization at the holistic level. This book offers four airline use cases to show how the topics discussed in different chapters can be applied by different types of airlines. As with Taneja's other publications, it provides a number of forewords and thought leadership pieces, contributed by practitioners, to elaborate on topics discussed in the book. This will be of interest to executives and senior managers within airlines, airports, and air transport supporting industries.
Keywords: Aeronautics, Commercial.; Airlines -- Management.; elektronické knihy; electronic books